Chemical quality and regulatory compliance of drinking water in Iceland - Gunnarsdottir, Maria J.; Gardarsson, Sigurdur M.; Jonsson, Gunnar St.; Bartram, Jamie (2016)
Assuring sufficient quality of drinking water is of great importance for public wellbeing and prosperity. Nations have developed regulatory system with the aim of providing drinking water of sufficient quality and to minimize the risk of contamination of the water supply in the first place. In this study the chemical quality of Icelandic drinking water was evaluated by systematically analyzing results from audit monitoring where 53 parameters were assessed for 345 samples from 79 aquifers, serving 74 water supply systems. Compliance to the Icelandic Drinking Water Regulation (IDWR) was evaluated with regard to parametric values, minimum requirement of sampling, and limit of detection. Water quality compliance was divided according to health-related chemicals and indicators, and analyzed according to size. Samples from few individual locations were benchmarked against natural background levels (NBLs) in order to identify potential pollution sources. The results show that drinking compliance was 99.97% in health-related chemicals and 99.44% in indicator parameters indicating that Icelandic groundwater abstracted for drinking water supply is generally of high quality with no expected health risks. In 10 water supply systems, of the 74 tested, there was an indication of anthropogenic chemical pollution, either at the source or in the network, and in another 6 water supplies there was a need to improve the water intake to prevent surface water intrusion. Benchmarking against the NBLs proved to be useful in tracing potential pollution sources, providing a useful tool for identifying pollution at an early stage.